Symptoms and sleep patterns during inpatient treatment of methamphetamine withdrawal: A comparison of mirtazapine and modafinil with treatment as usual - McGregor C. (2014)
The safety and tolerability of modafinil (400 mg/day, n = 14) and mirtazapine (60 mg/day, n = 13) in inpatient methamphetamine withdrawal treatment were compared to a historical comparison group receiving treatment as usual (pericyazine, 2.5-10 mg/day, n = 22). Modafinil and mirtazapine were well tolerated, producing minimal positive subjective effects and no discontinuation effects in this open-label study. Side effects were mild and transient. Aches and pains were most commonly reported by participants receiving mirtazapine, whereas headache was reported by modafinil-treated participants. Modafinil-treated participants had a milder withdrawal syndrome as measured by the Amphetamine Cessation Symptom Assessment and less sleep disturbance in comparison to mirtazapine. Pericyazine was associated with a more severe withdrawal syndrome in comparison to mirtazapine and modafinil. Both modafinil and mirtazapine were safe and well tolerated in methamphetamine withdrawal treatment. However, these early findings of efficacy in symptom amelioration should be replicated in an adequately powered, randomized, placebo-controlled double-blind design. © 2008 Elsevier Inc. All rights reserved.